Political Corruption as a Real Threat to the Sustainability of Constitutional Democracy - Agustina, Enny; Mallaranggeng, Andi Bau; Rais, Muslihin; Rasyid, Muh. Fadli Faisal; Khair, Otti Ilham; Rivera, Kevin M; Kartika, Arie (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study aims to examine the impact of political corruption on citizens' capacity to participate in government, the efficacy of anti-corruption laws, and the role of the Corruption Eradication Commission in the fight against corruption and the strengthening of constitutional democracies in Indonesia.Examining applicable legal standards, legislation, rules, doctrine, and judicial decisions is part of the normative research strategy. This examination also included a literature review of relevant studies, articles, and government publications. The research found that corruption discourages citizens of Indonesia from becoming active in politics. The public has lost interest in politics and has become wary of the corrupt system as a result. When it comes to creating a transparent and honest political system, there are doubts about how successful anti-corruption laws and the Corruption Eradication Commission have been in eradicating political corruption.